Identification of Lactobacillus proteins with different recognition patterns between immune rabbit sera and nonimmune mice or human sera - Górska, Sabina; Buda, Barbara; Brzozowska, Ewa; Schwarzer, Martin; Srutkova, Dagmar; Kozakova, Hana; Gamian, Andrzej (BMC microbiology, 2016)
BACKGROUND: The genus Lactobacillus belongs to a large heterogeneous group of low G + C Gram-positive anaerobic bacteria, which are frequently used as probiotics. The health-beneficial effects, in particular the immunomodulation effect, of probiotics depend on the strain and dose used. Strain variations may be related to diversity of the cell surface architecture of bacteria and the ability to express specific antigens or secrete compounds. The use of Lactobacillus as probiotic requires a comprehensive understanding of its effect on host immune system. To evaluate the potential immunoreactive properties of proteins isolated from four Lactobacillus strains: L. johnsonii 142 and L. johnsonii 151, L. rhamnosus LOCK 0900 and L. casei LOCK 0919, the polyclonal sera obtained from mouse and human have been tested as well as with sera from rabbits immunized with whole lactobacilli cells. RESULTS: The reactivity of isolated proteins detected by SDS-PAGE and Western blotting was heterogeneous and varied between different serum samples. The proteins with the highest immunoreactivity were isolated, purified and sequenced, in particular the fractions were identified as phosphoglycerate kinase (L. johnsonii 142), glyceraldehyde 3-phosphate dehydrogenase (L. johnosnii 142, L. rhamnosus LOCK 0900), hypothetic protein JDM1_1307 (L. johnsonii 151) and fructose/tagatose-bisphosphate-aldolase (L. casei LOCK 0919). CONCLUSION: The different prevalence of reactions against tested antigens in rabbit, mouse and human sera may indicate significant differences in immune system and commensal cross-talk in these groups. The identification of immunoreactive lactobacilli proteins opens the possibility to use them as an antigens for development of vaccines.
Keywords: Bacterial Proteins; antisérum; myši; elektroforéza v polyakrylamidovém gelu; Immune Sera; Electrophoresis, Polyacrylamide Gel; zvířata; Humans; Mice; králíci; bakteriální proteiny; Lactobacillus; Rabbits; lidé; Animals